Management of company finance - Samuels, J. M. (John Malcolm), 1938-; Wilkes, F. M.; Brayshaw, R. E. (London ; Boston : International Thomson Business Press, 1996)
This book is about: The financial environment; Flow of funds and taxation; Finance and accounting; Investment appraisal; Capital rationing ans risk analysis in imperfect capital markets; ...
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance; Business enterprises -- Finance -- Case studies